2003
DOI: 10.1002/chem.200390144
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Catalysis: A Mechanistic Study of β‐Lactone Synthesis from Epoxides and CO—Insights into a Difficult Case of Homogeneous Catalysis

Abstract: Carbonylation of epoxides with a combination of Lewis acids and cobalt carbonyls was studied by both theoretical and experimental methods. Only multisite catalysis opens a low-energy pathway for trans opening of oxirane rings. This ring-opening reaction is not easily achieved with a single-site metal catalyst due to structural and thermodynamic constraints. The overall reaction pathway includes epoxide ring opening, which requires both a Lewis acid and a tetracarbonylcobaltate nucleophile, yielding a cobalt al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…The function of the chromium complex is of a dedicated Lewis acid that polarizes and activates the epoxide, and is capable of forming a stable metalate complex. The reaction has major similarities to what has been described for the formation of lactones from epoxides and CO. [67] The activation barrier for the nucleophilic attack is negligible ( (Table 1). Likewise, it was found that the ring-opening event occurred easily.…”
Section: Theoretical Studymentioning
confidence: 98%
“…The function of the chromium complex is of a dedicated Lewis acid that polarizes and activates the epoxide, and is capable of forming a stable metalate complex. The reaction has major similarities to what has been described for the formation of lactones from epoxides and CO. [67] The activation barrier for the nucleophilic attack is negligible ( (Table 1). Likewise, it was found that the ring-opening event occurred easily.…”
Section: Theoretical Studymentioning
confidence: 98%
“…We have previously reported in experimental and theoretical studies on the control of the product distribution by choice of the proper Lewis acid. [7,9] The intermediate species LA-O-CH(CH 3 )-CH 2 -CO-Co(CO) 4 (2), that Abstract: The cobalt-catalyzed alternating copolymerization of epoxides and CO is a novel, direct approach to aliphatic polyesters, such as poly(hydroxybutyrate) (PHB). This reaction was found to be catalyzed by Ph 3 Si-[Co(CO) 4 ] (4) and pyridine affording in a first step the stable mono-insertion product Ph 3 Si-O-CH(CH 3 )-CH 2 -COCo(CO) 4 (5).…”
Section: Introductionmentioning
confidence: 99%
“…[9] At this stage, for many systems, lactone formation is the next step in the catalytic cycle. However, in the presence of a base/nucleophile such as pyridine, the situation is different and polymer is produced.…”
mentioning
confidence: 99%
See 2 more Smart Citations